2022
DOI: 10.3390/jcm11144006
|View full text |Cite
|
Sign up to set email alerts
|

Von Willebrand Factor and ADAMTS-13 Are Associated with the Severity of COVID-19 Disease

Abstract: Coagulopathy in COVID-19 patients is presumably based on systemic hypercoagulation with the inflammatory response. As a result of endothelial dysfunction, tissue factor and von Willebrand factor (vWF) are released into the blood stream, which leads to prothrombinase activation. The vWF/ADAMTS-13 ratio can be used for monitoring the severity of the disease. This observational prospective study included 141 patients with COVID-19. In patients with mild COVID-19 (group 1), the assessment was performed on the 3rd–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…84 Indeed, numerous studies have reported elevated levels of vWF in COVID-19 patients. [28][29][30][32][33][34] On the other hand, decreased levels of ADAMTS13 has been detected in these patients, 31,47,48 and ratio of vWF antigen to ADAMTS13 activity is reportedly elevated in them. 6,49 Joly et al highlighted that increased vWF antigen to ADAMTS13 activity ratio is correlated with mortality, 34 while Mancini et al reported that imbalance between vWF antigen and ADAMTS13 activity is associated with disease severity.…”
Section: Von Willebrand Factor and Adamts13 Axismentioning
confidence: 83%
See 4 more Smart Citations
“…84 Indeed, numerous studies have reported elevated levels of vWF in COVID-19 patients. [28][29][30][32][33][34] On the other hand, decreased levels of ADAMTS13 has been detected in these patients, 31,47,48 and ratio of vWF antigen to ADAMTS13 activity is reportedly elevated in them. 6,49 Joly et al highlighted that increased vWF antigen to ADAMTS13 activity ratio is correlated with mortality, 34 while Mancini et al reported that imbalance between vWF antigen and ADAMTS13 activity is associated with disease severity.…”
Section: Von Willebrand Factor and Adamts13 Axismentioning
confidence: 83%
“…We reviewed 7 studies 10,31,34,40,46–48 examining the serum levels of ADAMTS13 antigen among 651 patients (136 with poor outcome and 515 with good outcome). The pooled standard mean difference between the two groups was −0.69 (−0.90, −0.47) ( p < 0.00001), indicating the decreased ADAMTS13 antigen levels in critically ill patients (Figure 2, panel C).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations